21st International Conference on Offshore Mechanics and Arctic Engineering, Volume 1 2002
DOI: 10.1115/omae2002-28151
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Integration of Analysis and Design of Mooring Systems and Risers: Part II — Studies on a DICAS System

Abstract: The objective of this paper is to study different analysis methodologies for the design of floating production systems. The main issues are the use of uncoupled and coupled analysis methods, and the integration in the analysis and design of the mooring system and the risers. This paper is a companion to another paper also presented in the OMAE2002 Conference [1]. That paper describes a “basic” classic, uncoupled methodology, and comments on some refinements in the representation of the behavior of the lines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…[10,11], even these refinements still involve several simplifications. They fail to completely represent the non-linear dynamic interaction between vessel and lines (including for instance the nonlinear behaviour of the damping of the lines that influence the LF motions of the vessel).…”
Section: Uncoupled Methodologymentioning
confidence: 98%
See 1 more Smart Citation
“…[10,11], even these refinements still involve several simplifications. They fail to completely represent the non-linear dynamic interaction between vessel and lines (including for instance the nonlinear behaviour of the damping of the lines that influence the LF motions of the vessel).…”
Section: Uncoupled Methodologymentioning
confidence: 98%
“…optimized time-domain methods including adaptive time-step variation [22e25], or frequency-domain methods [26e28]), the goal of obtaining a balance between accuracy and computational efficiency has also been sought by proposing "hybrid" analysis methodologies combining the use of coupled and uncoupled tools. Different procedures may be included into this classification [29,10,11,30,31]. In this work we will consider the "coupled motion analyses" [29,11,31] and the "semi-coupled analyses" [32] that will be described next.…”
Section: Hybrid Methodologies; Simplified Coupled Analysesmentioning
confidence: 99%
“…Recently, researchers have been acknowledging that the design of FPS should consider the fact that the moored system and the risers comprise a truly integrated system, that is, the overall behaviour of a floating system is dictated not only by the hydrodynamic behaviour of the hull, but also by its interaction with the hydrodynamic/structural behaviour of the lines [1][2][3][4][5][6][7][8][9][10]. Throughout the last decade, Petrobras (the Brazilian state oil company) have recognized this need of formulating and developing a computational system for the coupled numerical simulation of FPS.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Senra et al [1], Correa et al [2], Correa [12], and Senra [13] describe alternative design methodologies, in increasing order of complexity, considering different levels of integration between hull, mooring lines and risers.…”
Section: Introductionmentioning
confidence: 99%
“…Among these simplified analysis methods is the uncoupled analysis, e.g., Ormberg and Larsen(1998) showed that results from the uncoupled analysis have a reasonable degree of accuracy when considering current forces and low-frequency damping contributions from moorings and risers as additional loads on the platform. Correa et al (2002) proposed a numerical free decay test to estimate the equivalent inertia and damping coefficients used in the uncoupled method. The frequency-domain approach has also gained much attention as a practical method because of its computational efficiency.…”
Section: Introductionmentioning
confidence: 99%